Implementasi Early Warning System (Ews) dalam Mendeteksi Perburukan Akut pada Pasien Dewasa di Ruang Rawat Inap Rumah Sakit - Lia Puji Astuti; Yanny Trisyani; Ristina Mirwanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this scoping review is to identify how the application of EWS to detecting acute deterioration in adult patients in general ward hospital. The method used was a scoping review and the literature has been obtained from searches derived from four databases originating from PubMed, Scopus, Sage, and CINAHL. The results showed that the implementation of EWS consisted of 6 components (vital sign recording, EWS scoring and reading, EWS protocol, clinical response based on escalation protocol, information assistance process using bundle communication (SBAR), medical emergency team (MET) system activation). Seven main of vital sign have to measured are respiratory rate, oxygen saturation, oxygen supplementation, temperature, pulse, systolic blood pressure, and level of consciousness. Persistence and additional commitment since 2009 were identified as significantly increasing benefits during the implementation of EWS instruments to improve patient outcomes. This success was obtained from experience that can increase the knowledge and competence of nurses. Changes in the risk of the EWS score can be read by nurses as an indication of clinical deterioration that requires stabilization interventions. Innovations have also been carried out since 2013 which have been successfully implemented in various countries, especially in 2019 and 2021 which are called EWS electronic. Based on this study, EWS proved to be accurate in detecting deterioration in patients. Therefore, to improve the implementation of EWS nurses must have good knowledge, because in implementing EWS requires critical thinking, and the ability to analyze numerical score classifications as a basis for decision making. Keywords: Early Warning System, EWS, Nurse Implementation, Patient deterioration.